The Impact Of Project-Based Learning On Reflective Skills And Visual Communication In Accounting Education: Dampak Pembelajaran Berbasis Proyek Terhadap Keterampilan Reflektif Dan Komunikasi Visual Dalam Pendidikan Akuntansi - Nurul Hidayah; Ani Widayati; Niken Purnamasari; Ratna Rosita Pangestika (Universitas Negeri Yogyakarta, 2026)
Higher education institutions are expected to adopt learning strategies that go beyond academic mastery to cultivate reflective, communicative, and creative abilities as key 21st-century competencies. This study describes the implementation of Project-Based Learning (PjBL) integrating reflective essay writing and academic poster design, and examines its effects on students’ reflective skills, visual communication, and professional literacy. A mixed-method approach with a sequential explanatory quasi-experimental design was used. Participants were 107 students from the Accounting Education Study Program at Yogyakarta State University, divided into an experimental class (55 students) and a control class (52 students). The four-week intervention followed four stages: concrete experience, reflective observation, abstract conceptualization, and active experimentation. Data were gathered through questionnaires, artifact analysis (essays and posters), classroom observations, and semi-structured interviews. Results indicate that multimodal PjBL significantly improved students’ critical reflection. Qualitative findings show that combining written reflection with visual expression enabled students to connect theory and practice more meaningfully, increased learning motivation, and strengthened professional awareness, particularly in using academic English. The study confirms that multimodal PjBL is an effective and innovative approach in higher-education ESP instruction. It recommends broader and longer implementation in Accounting courses to enhance employability skills and better align learning with professional workplace demands.